Gambaran faktor eksternal yang berhubungan dengan kejadian stunting pada anak usia 24 – 59 bulan di Wilayah Kerja Puskesmas Tepus II Gunungkidul - Wahyudi, Wahyudi; Khoeriyah, Salis Miftahul; Monika, Rika (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Background: The incidence of stunting among children under five in the world is estimated at 149.2 million (22%) and the prevalence of stunting in Indonesia ranks third highest in Southeast Asia. The impact of stunting is an obstacle in achieving optimal growth and development. Objective: To determine the description of external factors that influence the incidence of stunting in toddlers aged 24-59 months in the working area of ​​the Tepus II Public Health Center Gunungkidul Methods: This research used a descriptive study with a cross sectional approach. Sampling using total sampling, all mothers who have toddlers aged 24-59 months with short and very short criteria in the work area of ​​the UPT Puskesmas Tepus II Gunungkidul as many as 59 respondents. Data analysis used univariate analysis Results: the mother's education level is mostly low as many as 36 respondents (61.02%), the number of respondent's family members is at most more than 4, namely 34 respondents (57.63%), the respondent's family income is at most less than Rp. 1,705,000 (less than the minimum wage) i.e. 44 respondents (74.58%), most of the stunting toddlers amounting to 48 (81.36%) received exclusive breastfeeding, and the majority of family marriage age was more than 19 years, namely 36 respondents (61, 02%). Conclusion: External factors related to the incidence of stunting in toddlers aged 24-59 months in the working area of ​​the Tepus II Gunungkidul Health Center include most of the mothers with low education, having more than 4 family members, income below the minimum wage, getting exclusive breastfeeding and age of marriage are > 19 years old.